1997
DOI: 10.1021/jp9703420
|View full text |Cite
|
Sign up to set email alerts
|

Distance Dependence and Spatial Distribution of the Molecular Quadrupole Moments of H2, N2, O2, and F2

Abstract: We have estimated the complete basis set limits for the Hartree-Fock, MP2, CASSCF, and CASSCF+1+2 wave functions for the titled molecules and calculated the molecular quadrupole moment as a function of bond length. Our recommended values for Θ (V)0,J)0) compare favorably to the current experimental values and previous high-level calculations. To aid in the analysis of the relationship between the molecule's electronic structure and quadrupole moment, we introduce the concept of a quadrupole moment density that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 50 publications
0
31
1
Order By: Relevance
“…Several groups have calculated these moments using a variety of methods and their values are often very different from ours. For Li 2 our value for Q 2 is 36% smaller than the numerical Hartree-Fock value given by Sundholm et al 23 This difference could possibly be ex- 34 Although our wave function captures a greater percentage of the correlation energy than either of these earlier calculations our value for Q 2 is 31% larger than the one given by Maroulis and Thakkar and our value for Q 4 is 39% larger. This discrepancy is not an isolated one.…”
Section: Propertiescontrasting
confidence: 73%
“…Several groups have calculated these moments using a variety of methods and their values are often very different from ours. For Li 2 our value for Q 2 is 36% smaller than the numerical Hartree-Fock value given by Sundholm et al 23 This difference could possibly be ex- 34 Although our wave function captures a greater percentage of the correlation energy than either of these earlier calculations our value for Q 2 is 31% larger than the one given by Maroulis and Thakkar and our value for Q 4 is 39% larger. This discrepancy is not an isolated one.…”
Section: Propertiescontrasting
confidence: 73%
“…A theoretical study [53] found H 0 ¼ 0:959 a.u. for neutral N 2 (X), in perfect agreement with H 0 ¼ 0:95AE 0:02 a.u.…”
Section: Molecular Electric Quadrupole Momentsmentioning
confidence: 99%
“…for neutral N 2 (X), in perfect agreement with H 0 ¼ 0:95AE 0:02 a.u. (average of four intensity measurements, Table 8 in [53]). …”
Section: Molecular Electric Quadrupole Momentsmentioning
confidence: 99%
“…These interactions are simplified by using 'atom-atom' approximation, for H 2 molecules, which are represented by two H atoms. The electrostatic interaction between H 2 molecules is modeled by assigning point dipoles of strength 0.4174 placed at each atomic site and directed along the H 2 bond axis away from the center of mass to reproduce the molecular quadrupole moment of H 2 [7]. The repulsion and dispersion interactions between molecules are modeled using the Buckingham formula, U(r) = A exp(Àbr) À C 6 /r 6 where r is the distance between hydrogen atoms, C 6 is the London dispersion coefficient, and A and b, are the Born-Mayer parameters.…”
Section: Interaction Potentialmentioning
confidence: 99%